2017
DOI: 10.1002/chem.201605495
|View full text |Cite
|
Sign up to set email alerts
|

NHC‐Stabilised Acetylene—How Far Can the Analogy Be Pushed?

Abstract: Experimental studies suggest that the compound (NHC ) C H can be considered as a complex of a distorted acetylene fragment which is stabilised by benzoannelated N-heterocyclic carbene ligands (NHC )→(C H )←(NHC ). A quantum chemical analysis of the electronic structures shows that the description with dative bonds is more favourable than with electron-sharing double bonds (NHC )=(C H )=(NHC ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 111 publications
(62 reference statements)
2
37
0
Order By: Relevance
“…nature is not directly apparent. [27][28][29][30][31][32][33][34][35][36][37] Tables S4-S6 show that the DE orb values using atom Minthe electronic ground state and (Bz) 3 in the excited state are significantly larger than those in Table 4. However,t here is an alternative option for the choice of the interacting fragments.T he calculated partial charges of M(Bz) 3 using the NBO 6.0 method [38] suggest large positive charges for the metal atoms of 1.47 for Ca, 1.46 for Sr and 1.40 for Ba.…”
Section: Termmentioning
confidence: 87%
See 1 more Smart Citation
“…nature is not directly apparent. [27][28][29][30][31][32][33][34][35][36][37] Tables S4-S6 show that the DE orb values using atom Minthe electronic ground state and (Bz) 3 in the excited state are significantly larger than those in Table 4. However,t here is an alternative option for the choice of the interacting fragments.T he calculated partial charges of M(Bz) 3 using the NBO 6.0 method [38] suggest large positive charges for the metal atoms of 1.47 for Ca, 1.46 for Sr and 1.40 for Ba.…”
Section: Termmentioning
confidence: 87%
“…Our experience in numerous studies has shown that the EDA-NOCV calculations are not very sensitive to the functional. [27][28][29][30][31][32][33][34][35][36][37] Table 4gives the numerical results of the calculations of M(Bz) 3 (M = Ca, Sr, Ba) at the D 3 equilibrium structures.…”
Section: Modementioning
confidence: 99%
“…The method has been found useful in several molecules where the nature of the bonding interactions is not obvious. The reader may find further examples in the literature …”
Section: The Eda–nocv Methodsmentioning
confidence: 99%
“…Those fragments, which yield the smallest orbital interaction energy, indicate the most faithful model for the bonding situation. This was particularly useful in cases for which the description in terms of dative bonds A→B or electron‐sharing bonds A−B was not clear ,…”
Section: Introductionmentioning
confidence: 99%